2016
DOI: 10.1109/jsyst.2015.2435994
|View full text |Cite
|
Sign up to set email alerts
|

QoE Power-Efficient Multimedia Delivery Method for LTE-A

Abstract: Abstract-The fastest growing of multimedia services over future wireless communication system demand more network resources, efficient delivery of multimedia service with high users satisfaction, and power optimization of User Equipments (UEs). The resources and power optimization are significant in future mobile computing systems, because emerging multimedia services consume more resources and power. The 4G standard of LTE-A wireless system has adopted the Discontinuous Reception (DRX) method to extend and op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Nguyen et al [15] further showed several benefits of TCP congestion protocol algorithms in controlling congested traffic. Moreover, TCP CUBIC was described as the next generation of algorithms with good behavior in controlling congestion towards providing better throughput results; while TCP YeAh was illustrated as the congestion control algorithm with an ability to adjust itself in two kinds of conditions: long and short round-trip time (RTT) [16]- [18]. It acts as TCP New Reno in long RTT by prioritizing network connection stability through a reduction in the delay, which also decreases the throughput as a form of tradeoff.…”
Section: Related Workmentioning
confidence: 99%
“…Nguyen et al [15] further showed several benefits of TCP congestion protocol algorithms in controlling congested traffic. Moreover, TCP CUBIC was described as the next generation of algorithms with good behavior in controlling congestion towards providing better throughput results; while TCP YeAh was illustrated as the congestion control algorithm with an ability to adjust itself in two kinds of conditions: long and short round-trip time (RTT) [16]- [18]. It acts as TCP New Reno in long RTT by prioritizing network connection stability through a reduction in the delay, which also decreases the throughput as a form of tradeoff.…”
Section: Related Workmentioning
confidence: 99%
“…QoE is highly applicationand user-specific with an adequate level of reliability. It is required in 5G to provide end users with better experience and satisfaction in a wireless network [41], [68], [69].…”
Section: B Performance Requirements Of 5g Wireless Networkmentioning
confidence: 99%
“…To address (23) through ALM, the Lagrangian function can be given by ( 24) on top of the next page. By updating the Lagrangian multipliers following [16] after some iterations, the duality gap will be zero, Karush-Kuhn-Tucker (KKT) conditions hold which yields a sub-optimal solution [17].…”
Section: (20)mentioning
confidence: 99%
“…Fig. 2(c) shows the convergence behavior of proposed algorithm for two values of the number of subcarriers with related rating factor [23] in each case is calculated. In Fig.…”
Section: ) Web Service Assessmentmentioning
confidence: 99%